Analytical justifications of constructive parameters of bionic colters for vertical soil treatment - Aliiev, Elchyn; Алієв, Ельчин Бахтияр огли; Tesliuk, Hennadii; Теслюк, Геннадій Володимирович (Національний університет біоресурсів і природокористування України, 2024)
Bionic coulters imitate natural forms and functions, which help reduce energy costs for soil tillage. The aim of the research was to justify the design and structural parameters of turbo discs (coulters) for vertical tillage based on the principles of bionic reverse engineering. Using this method, an equation for the shape of the turbo discs (coulters) was derived, which was obtained by approximating the shell of the argonaut (Argonauta argo). The equation takes into account the main structural parameters of the turbo discs: diameter Dd, cutout height Hm, wave height Hw, number of cutouts n, and spiral coefficient k. As a result of analytical studies on the interaction process between a solid disc and plant residues, the optimal diameter value was determined to be Dd=460 mm under the condition of submerging stems with a thickness of 10-20 mm to a depth of 80 mm. The analytical studies confirmed that the presence of cutouts on the disc prevents stem deflection and ensures better stem capture. In analysing the obtained dependencies using the Wolfram Cloud software package, the optimal values for the cutouts were determined: cutout height Hm=40 mm, number of cutouts n=8. The presence of waves on the disc surface ensures that the interaction with plant residues is independent of their position on the field surface and creates conditions for vertical soil tillage. It was found that, to minimize specific cutting resistance and maximize the degree of soil fragmentation, the optimal wave parameters for the coulter are a wave height of Hw=24.4 mm. The justified parameters of the coulters provide the best balance between soil fragmentation efficiency and reduction in energy consumption for soil tillage. The obtained results can be used to adapt existing agricultural machinery to the new structural parameters of coulters to improve its efficiency. Біонічні колтери імітують природні форми та функції, які дозволяють знизити енергетичні витрати на обробку ґрунту. Мета досліджень була обґрунтування конструкції і конструктивні параметри турбодисків (колтерів) для вертикального обробітку ґрунту спираючись на принципи біонічного зворотного інжинірингу. Враховуючи цей метод визначено рівняння форми турбодисків (колтерів), яке отримано в результаті апроксимації мушлі аргонавта (Argonauta argo). Рівняння враховує основні конструктивні параметри турбодисків: діаметр Dd, висота вирізу Hm, висота хвилі Hw, кількість вирізів n, коефіцієнт спіралеподібності k. В результаті аналітичних досліджень процесу взаємодії суцільного диска з рослинними рештками визначено раціональне значення його діаметра Dd=460 мм при умові занурення стебелів товщиною 10-20 мм, на глибину 80 мм. Аналітичні дослідження підтвердили, що наявність вирізів на диску унеможливлює відштовхування стебла і забезпечує його кращій захват. При цьому аналізуючи отримані залежності у програмному пакеті Wolfram Cloud визначені раціональні значення вирізів: висота вирізу Hm=40 мм, кількість вирізів n=8. Наявність хвиль в площині диску забезпечує незалежність процесу взаємодії з рослинними залишками від їх розташування на поверхні поля та створює умови для вертикальної обробки ґрунту. Встановлено, що при умові мінімізації питомого опору різання і максимізації ступеня подрібнення ґрунту раціональними параметрами хвилі колтера є висота хвилі Hw=24,4 мм. Обґрунтовані параметри колтерів забезпечують найкращий баланс між ефективністю подрібнення ґрунту і зниженням енергетичних витрат на обробку ґрунту. Отримані результати можна використати для адаптування існуючої сільськогосподарської техніки під нові конструктивні параметри колтерів для підвищення її ефективності.
Аналітичні обґрунтування конструктивних параметрів біонічних колтерів для вертикального обробітку ґрунту
Keywords: vertical tillage; вертикальний обробіток ґрунту; turbo disc; турбодиск; shape; форма; shell; мушля; argonauts; аргонавти; аналітичні дослідження; analytical studies